UPAYA MARKETING PUBLIC RELATIONS PERUSAHAAN-PERUSAHAAN E-COMMERCE TERBAIK DI INDONESIA DALAM MEMPERTAHANKAN BRAND REPUTATION DI MATA KONSUMEN - Ratna Sari, Siti Dewi Sri; Haryanti, Astrid (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study used a qualitative approach with descriptive research which described reputation’s elements based on the concept from Urde and Greyser. The primary data collecting method was a semi-structured interview through a Focus Group Discussion with consumers, enriched with digital observation. The study results show that the efforts of Tokopedia.com’s MPR in maintaining brand reputation towards consumers’ view are the best compared to Lazada.co.id and Blibli.com as this company has the highest scores on almost reputation elements. The efforts of Lazada.co.id’s MPR as the first rank of best e-commerce companies in Indonesia is the weakest. It is recommended to increase the clarity in communicating all brands’ values through various organized MPR’s activities and to provide customer service for better interaction with consumers. Keywords: marketing public relations, e-commerce, brand reputation, the consumer.